THE EFFECT OF TRIAGE ON PAEDIATRIC WAITING TIMES IN A PAEDIATRIC ASSESSMENT UNIT. Issue 12 (23rd November 2015) - Brittain, C; Forster, A
Abstract : Objectives & Background: Our hospital is in the process of increasing the number of hours its paediatric assessment unit (PAU) remains open in order to help patient flow within the emergency department. Previously we have used our ward based Paediatric Early Warning Score (PEWS) charts to triage these patients. However, in view of the increased demand on the department, a more PAU focussed triage tool was deemed necessary to primarily improve patient safety, but also patient experience through reducing waiting times. Whilst various paediatric triage tools have been developed for use within paediatric emergency departments, we could not find a tool for use within the PAU, which primarily sees the unwell rather than the injured child. Our aim was to assess whether we could construct a triage tool to identify the unwell child in order to result in them being seen sooner by a member of the medical team. We also hoped it would improve waiting times compared with the currently used PEWS method. Methods: We devised a triage tool that was suitable for our PAU. This was based on The Emergency Severity Index, Leicester's Paediatric Observation Priority Score, the Modified Manchester Triage system, and the PEWS and Paediatric Acute Warning Score (PAWS) charts that are already in use within our hospital. We then compared waiting times for children to be seen who were assessed by the previously used PEWS, with those assessed with the triage tool. We also compared our breaches for waiting within the department for more than 6 hours. Results: For the week of the PEWS scoring, 89% had a PEWS 0–1, 5% had a score of 2–3, and 6% of 4+. The mean length of time to be seen was 39 min, 29 min and 0 min respectively. For the week using our triage tool, 69% scored green, 22% amber and 9% red. Average time to be seen was 44 min, 22 min and 32 min respectively. Using the PEWS method, senior review was outside the target time of two hours in 16%, compared with 3.7% with the triage tool. Patients were staying more than the recommended 6 hours in 5.8% of cases with PEWS and 2.96% with the triage tool. Conclusion: Our triage tool appears to have improved breaches for time to senior review and as such has resulted in a reduction in length of stay within the department; thus improving patient turnover and flow between the emergency department and PAU. It has not however, improved the speed at which the unwell child is reviewed, this may be due to poor specificity of the tool.